Interventional bundle for venous thromboembolism prevention: ensuring quality and effectiveness. Issue 2 (21st June 2019) - Shapiro, Susan; Dunnigan, Anna; Keen, Sarah; Clarke, Penney
Abstract : Hospital-associated thromboses (HATs) are a potentially preventable cause of morbidity and mortality. Oxford University Hospitals NHS Foundation Trust was designated a Venous Thromboembolism (VTE) Exemplar Centre by NHS England in 2014. However, following delayed reporting of a potentially preventable HAT in 2015, a benchmarking exercise suggested HATs were being under-reported, and also that the established hospital-wide audits of VTE prevention had significant limitations. The aim of this interventional bundle was to ensure high-quality data for key VTE prevention measures across the hospital, to identify areas for improvement and demonstrate a reduction in the number of potentially preventable HATs over a 2-year period. The project team engaged with hospital leadership and collaborated with hospital-wide stakeholders. A multifaceted approach was taken and 'Plan Do Study Act' cycles were used to test interventions with continuous evaluation of impact. The percentage of inpatients receiving appropriate thromboprophylaxis progressively increased from 94% to 98%. The project did not achieve its secondary aim of a reduction in the number of potentially preventable HATs. Revision of the HAT reporting process resulted in better detection and an initial increase in reporting of potentially preventable HATs, although data suggest that the level of harm from errors is now reducing. The improvement in overall appropriate thromboprophylaxis is considered to be due to robust audits of appropriate thromboprophylaxis, upskilling of ward pharmacists, improved detection of potentially preventable HATs resulting in additional safety nets such as linking the 'outcome recommendation' of the electronic VTE risk assessment directly to electronic prescribing, and increased awareness and education. Combining low-cost actions in a coordinated interventional bundle has produced measurable improvements in our VTE management programme, enhancing patient safety. We believe the model to be sustainable and replicable in other general hospitals.